Od SSKJ do spletnega portala standardne slovenščine - Krek, Simon (Jezik in slovstvo, 2009)
In the article we treat the state of reference sources for Slovene language and outline a proposal for a programme for constructing a portal of interconnected language sources in electronic form. The proposal is conceived in four sections, embracing the areas of language description, the standardisation of language, and terminological and bilingual sources. We briefly sketch the development of similar sources for other languages and give examples of these sources in particular fields. We find that the state of development of sources for Slovene is inadequate, as is the access to these sources, and conclude that improvement of this situation would be aided by more imaginative planning and the existence of a central institutional body with a capacity for the genuine provision of financial resources.
Keywords: computational linguistics; Corpus linguistics; estonščina; jezikovni priročniki; jezikovni viri; jezikovno načrtovanje; korpusno jezikoslovje; primerjalne študije; računalniško jezikoslovje; Slovene; slovenščina; sociolinguistics; sociolingvistika